Production of methane and gaseous compounds by surface microbial activity in a small pockmark field, Dunmanus Bay, Ireland. (5th July 2021) - O'Reilly, S.S.; Jordan, S.F.; Monteys, X.; Simpson, A.J.; Allen, C.C.R.; Szpak, M.T.; Murphy, B.T.; McCarron, S.G.; Soong, R.; Wu, B.; Jenne, A.; Grey, A.; et al.
Abstract: Marine pockmarks are globally widespread seabed depressions, conventionally thought to be formed by the accumulation and expulsion of microbial and thermogenic gas. However, other putative fluids and processes have been implicated in pockmark formation and gas escape to the atmosphere may be underestimated. Given the complex spectrum of aquatic settings, morphologies and sizes, there may also exist a spectrum of physical, chemical and biological processes that form pockmarks. Pockmarks in shallow coastal waters are now understood to be widespread, but the influence of physical dynamics (e.g. tides, storms, etc.), terrestrial processes and anthropogenic activities add considerable spatiotemporal complexity and uncertainty to our understanding of these features. Here, we revisit a field of small (ca. 2 m diameter), shallow (<1 m depth) pockmarks in Dunmanus Bay, Ireland. The presence of muddy surface sediments overlying sand in the pockmarked area indicates that gas accumulation within fine-grained surface sediments contributes to formation of the features. Previous work indicates that CH4 is an important seepage fluid in Dunmanus and neighbouring bays. However, based on evidence from multiple surveys, we observe considerable spatiotemporal complexity, and the transient nature of the gas within sediments points to the potential for fluids other than traditional microbial or thermogenic CH4, migrating from sources tens to hundreds of metres below the seafloor. We observed atypical porewater profiles where millimolar concentrations of H2 S concentrations are observed in surface sediments in the absence of SO4 2− depletion, together with NH4 + build-up from ammonification of sedimentary organic matter. Archaeal methanogens, anaerobic methanotrophic archaea and SO4 2- -reducing Deltaproteobacteria co-occur in surface sediments in the pockmark field and NMR revealed the presence of non-competitive substrates for methanogens. We hypothesize that in - situ methanogenesis and production of other volatile metabolites besides CH4 (e.g. CO2, dimethyl disulfide) from microbial degradation of organic matter are potential gaseous fluids and could contribute to the formation of small pockmarks. Highlights: Pockmark field revisited at Dunmanus Bay, Ireland. Biogeochemical study of cores inside and outside the field. CH4, microbial diversity, porewater chemistry and organic matter composition reported. CH4, volatile metabolites, methanogens and methanotrophs in sediment with abundant SO4 2− . Surface microbial activity can produce diverse gaseous species and could play a role in small pockmark formation.